Cyclosporine A-resistant CAR-T cells mediate antitumour immunity in the presence of allogeneic cells - Yixi Zhang; Hongyu Fang; Guocan Wang; Guangxun Yuan; Ruoyu Dong; Jijun Luo; Yu Lyu; Yajie Wang; Peng Li; Chun Zhou; Weiwei Yin; Haowen Xiao; et al. (Nature Communications, 2023)
Abstract Chimeric antigen receptor (CAR)-T therapy requires autologous T lymphocytes from cancer patients, a process that is both costly and complex. Universal CAR-T cell treatment from allogeneic sources can overcome this limitation but is impeded by graft-versus-host disease (GvHD) and host versus-graft rejection (HvGR). Here, we introduce a mutated calcineurin subunit A (CNA) and a CD19-specific CAR into the T cell receptor α constant (TRAC) locus to generate cells that are resistant to the widely used immunosuppressant, cyclosporine A (CsA). These immunosuppressant-resistant universal (IRU) CAR-T cells display improved effector function in vitro and anti-tumour efficacy in a leukemia xenograft mouse model in the presence of CsA, compared with CAR-T cells carrying wild-type CNA. Moreover, IRU CAR-T cells retain effector function in vitro and in vivo in the presence of both allogeneic T cells and CsA. Lastly, CsA withdrawal restores HvGR, acting as a safety switch that can eliminate IRU CAR-T cells. These findings demonstrate the efficacy of CsA-resistant CAR-T cells as a universal, ‘off-the-shelf’ treatment option.